Rozwój Łodzi w perspektywie kandydatury na organizacje międzynarodowej wystawy Expo - Cysek-Pawlak, Monika Maria (Studia Miejskie, 2020)
The article opens the discussion about the strategic directions of the development of Lodz in the context of the application to organize the Expo 2022 put forward by the Polish government. The aim of the study is to assess the influence of the International Exposition on urban policy. The methodology rests on a careful analysis of the current activities carried out by the public authorities, both at the ministerial and city council levels. The juxtaposition of the adopted strategy in Lodz with the practical aspects of organizing the previous exhibitions forms an important part of the analysis. The study shows that the event focused on revitalisation may complement projects which are being introduced today. In the context of the dynamics of post-industrial city development, the Expo 2022 in Lodz may become an open platform for experience exchange and redefine the image of the analyzed area.